2002
DOI: 10.1034/j.1600-0897.2002.1o035.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased Levels of Macrophage Colony‐Stimulating Factor in the Placenta and Blood in Preeclampsia

Abstract: This is the first report concerning high placenta levels of M-CSF/ TP in preeclampsia. Increased M-CSF in the placenta supports the hypothesis that immunological abnormalities contribute to the etiology of preeclampsia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
23
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 33 publications
6
23
0
Order By: Relevance
“…We have found significantly increased levels of M-CSF in pre-eclampsia, and we are thus able to confirm the earlier findings described by Hayashi et al [21]. Keith et al [26] found unchanged levels in nulliparous and reduced levels in parous women, while we have observed marginally increased and unchanged M-CSF levels in nulliparous and parous women, respectively (data not shown).…”
Section: Cross-sectional Studysupporting
confidence: 93%
See 1 more Smart Citation
“…We have found significantly increased levels of M-CSF in pre-eclampsia, and we are thus able to confirm the earlier findings described by Hayashi et al [21]. Keith et al [26] found unchanged levels in nulliparous and reduced levels in parous women, while we have observed marginally increased and unchanged M-CSF levels in nulliparous and parous women, respectively (data not shown).…”
Section: Cross-sectional Studysupporting
confidence: 93%
“…More recently, however, several papers reporting reduced VEGF levels in pre-eclamptic pregnancies have appeared [34,35,46]. Reduced or less strongly increasing levels of macrophage colony-stimulating factor (M-CSF) between the first trimester and the time of labor have been associated with adverse pregnancy outcome and pre-eclampsia [26], while another study [21] found increased levels of this marker under similar clinical conditions. Insulin-like growth factor binding protein-1 (IGF-BP1) was found to be elevated in pre-eclampsia as a function of the severity of the disease in two reports [17,24], while in another study no such modification was observed [33].…”
Section: Introductionmentioning
confidence: 95%
“…More recently, however, reports on reduced VEGF levels in pre-eclamptic pregnancies seem to dominate [19,20]. Similarly, reduced or at least less strongly increasing levels of macrophage colonystimulating factor (M-CSF) [21] as well as increased serum levels of this marker [22] had been linked with the presence of pre-eclampsia. Insulin-like growth factor binding protein-1 (IGF-BP1) was found to be elevated in pre-eclampsia as a function of the severity of the disease in a couple of reports [23,24], while in another study no such effect was observed [25].…”
Section: Third-trimester Assessment Using Serum Markersmentioning
confidence: 95%
“…Various cytokines modify the trophoblastic functions [9] . We further reported that M-CSF levels were higher in preeclampsia patients than in normal pregnancies not only in maternal blood [10] but also in the placenta [7] . There were similar phenomena occurring in relation to granulocyte macrophage colony-stimulating factor (GM-CSF) [11] .…”
Section: Introductionmentioning
confidence: 96%
“…We previously reported that serum macrophage colony-stimulating factor (M-CSF) levels in peripheral blood increased with the progression of pregnancy [6] and that the placenta contained a large amount of M-CSF [7] . Many cytokines and growth factors have been detected in the uterus, placenta, or both in normal pregnancies [8] .…”
Section: Introductionmentioning
confidence: 99%